2014
DOI: 10.2174/1874149501408010105
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Energy Efficient Construction and their Influence on the Seismic Resistance of Light-weight Buildings

Abstract: Abstract:Recently, an increasing trend of passive and low-energy buildings transferring from non earthquake-prone to earthquake-prone regions has thrown out the question about the seismic safety of such buildings. The paper describes the most commonly used details of energy efficient construction, which could be critical from the point of view of earthquake resistance. The paper focuses on the prevention of ground floor slab thermal bridge and presents a case study on the seismic response of multi-storey woode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The models showing elastic behaviour were investigated in order to determine the maximum response of the foundation demand parameters such as the base displacement (D base ), whereas the nonlinear superstructure models were used for comparison of the superstructure demand parameters, such as the ductility demand (δ d ). It should be noted that such a selection was made according to [48,49], where it was shown that elastic models yield maximum base engineering demand parameters (EDPs), whereas inelastic models yield maximum superstructure EDPs. The seismic response of the structural models was evaluated by means of nonlinear time-history analyses considering a set of 30 real ground motion records (GMRs), which were selected so that they matched the target spectrum for stiff soil sites (soil type A in EC8 [50]), with 5% damping and a seismic intensity of 0.25 g. Incremental dynamic analyses (IDA) were performed for each selected GMR, with a variation step of 0.02 g up to a maximum seismic intensity of 1.0 g. Uni-directional dynamic analysis was adopted, which was best suited to the available results of the uni-directional experimental tests of the XPS material [31].…”
Section: Sdof Superstructure Modelmentioning
confidence: 99%
“…The models showing elastic behaviour were investigated in order to determine the maximum response of the foundation demand parameters such as the base displacement (D base ), whereas the nonlinear superstructure models were used for comparison of the superstructure demand parameters, such as the ductility demand (δ d ). It should be noted that such a selection was made according to [48,49], where it was shown that elastic models yield maximum base engineering demand parameters (EDPs), whereas inelastic models yield maximum superstructure EDPs. The seismic response of the structural models was evaluated by means of nonlinear time-history analyses considering a set of 30 real ground motion records (GMRs), which were selected so that they matched the target spectrum for stiff soil sites (soil type A in EC8 [50]), with 5% damping and a seismic intensity of 0.25 g. Incremental dynamic analyses (IDA) were performed for each selected GMR, with a variation step of 0.02 g up to a maximum seismic intensity of 1.0 g. Uni-directional dynamic analysis was adopted, which was best suited to the available results of the uni-directional experimental tests of the XPS material [31].…”
Section: Sdof Superstructure Modelmentioning
confidence: 99%
“…In such cases the expected top accelerations of the structure could increase by a factor of two or three in comparison with a structure on a fixed base. Such an increase could lead to damage to the superstructure or its content, which should not be ignored [1][2][3][4][5][6][7]. However, if the fundamental period of the superstructure is already on the plateau of constant accelerations, the insertion of TI under the foundation slab might prolong the structural period into the descending Proc.…”
Section: Foundation On Thermal Insulation Layersmentioning
confidence: 99%
“…1). An extensive description and schematic representation of other building structural details that might Vojko KILAR, Boris AZINOVIĆ and David KOREN University of Ljubljana, Faculty of Architecture Slovenia be critical from the point of view of earthquake resistance can be found in [1]. It has been therefore suggested, that the suitability of such details and technical solutions should be first verified from the viewpoint of their earthquake resistance before they are used in buildings in earthquakeprone areas.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, effective retrofitting concepts, which should include newly developed or modified and upgraded technologies, as well as new design concepts, need to be developed and their validity confirmed [4][5][6]. It should be mentioned that these technologies should also be considered from the seismic engineering point of view, since certain elements could influence the dynamic stability of a structure [7,8]. The specific properties and energy efficiency of such new technologies, as well as their design concepts, can be evaluated by the performance of different kinds of tests, especially when such measurements are combined with real case demonstrations [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%